Selection criteria for scientific periodicals for publication the manuscript in field of morphology. In help for author. - O. Yu. Pototskaya (Морфологія, 2015)
Background. Modern system of scientific work evaluation is based on scientometric indeces. It stimulates authors to choose journals for their manuscript publication, based on many parameters. Objective. To reveal convenient scientometric journals for native morphologists. Results. Analyzing main scientometric databases (Scopus, Web of Science and Russian Index of Scientific Citations) for the presence of journals, published in CIS countries, we have revealed their minimal number. This problem results in inadequate assessment of scientometric indices for native authors, as they publish their articles predominantly in another titles. Conclusion. Selecting a journal for manuscript publication authors should pay attention to its indexing in scientometric databases - Scopus, Web of Science and RISC. Among these journals, those which are published in CIS countries are more convenient for native authors. Among the three scientometric databases RISC is the most affordable – it contains the largest number of Ukrainian scientific periodicals and morphological journals of CIS countries. The fact of registering the journal in Google scholar or Index Copernicus International database is not enough to consider it as a scientometric.